2004
DOI: 10.1080/03078698.2004.9674305
|View full text |Cite
|
Sign up to set email alerts
|

Sexing and ageing Rose‐ringed ParakeetsPsittacula krameriin Britain

Abstract: Although Rose-ringed Parakeets Psittacula krameri over three years old can easily be sexed due to the males' rose-coloured neck-rings and black bibs, sexually immature males and females are considered impossible to separate in the hand. The biometrics of males and females overlap but males tend to be slightly larger than females in all measurements. We derived a discriminant function to separate the two sexes using wing length, bill length and the number of fully yellow underwing coverts. Biometrics were recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Psittacula k. manillensis is a 38-42 cm long (body + tail) parrot, with its tail accounting for about half of its length (∼25 cm; Butler 2005). In Europe, adult RRP generally weigh about 140 g (Butler and Gosler 2004). RRP on Kaua'i averaged 133 g, but 12 of the 17 individuals weighed were juveniles; the four adult males averaged 139 g (Gaudioso et al 2012).…”
Section: Distinguishing Featuresmentioning
confidence: 99%
“…Psittacula k. manillensis is a 38-42 cm long (body + tail) parrot, with its tail accounting for about half of its length (∼25 cm; Butler 2005). In Europe, adult RRP generally weigh about 140 g (Butler and Gosler 2004). RRP on Kaua'i averaged 133 g, but 12 of the 17 individuals weighed were juveniles; the four adult males averaged 139 g (Gaudioso et al 2012).…”
Section: Distinguishing Featuresmentioning
confidence: 99%
“…However, without carefully examining Rose-ringed Parakeets in the hand, it is not possible to separate sub-adult males from adult females (Butler & Gosler 2004) and so it is possible that multiple females were attending the nests. However, an examination of the Rose-ringed Parakeet specimens at the Natural History Museum, Tring reveals that there is a sub-adult specimen with a slightly enlarged testis, which may indicate that subadult male Rose-ringed Parakeets occasionally breed.…”
Section: Factors Affecting Reproductive Successmentioning
confidence: 99%
“…The subspecies P. k. parvirostris, which ranges from parts of Sudan east through northern Ethiopia and north-west Somalia, is similar but has a smaller beak and a somewhat greener, less yellowish head and cheeks (Ali and Ripley, 1969;Forshaw, 1978Forshaw, , 2010Fry and Keith, 1988). Butler and Gosler (2004) found that for Ring-necked Parakeets in the UK, female birds were characterized by a higher number of yellow underwing coverts, while juveniles could reliably be identified on the basis of their more pointed primary feathers.…”
Section: Descriptionmentioning
confidence: 99%